A PERFECT(IVE) INTERCORP: EQUIVALENTS OF CZECH VERBAL ASPECT IN PARALLEL CORPORA - Nováková, Eva (Bohemica Olomucensia, 2021)
The paper discusses the use of parallel corpora (InterCorp, a subcorpus of Czech National Corpus) in translation. It focuses on advantages and drawbacks of exploiting corpus data for a specific translation task, i.e., presenting a language-specific grammatical category of the Czech aspect to L2 Czech learners via English as the auxiliary language.
Keywords: corpus analysis; translation quality assessment; verbal aspect; contrastive functional analysis